Tunnelling in soft clay : a study of the tunnelling work under Kallang Basin in the circle line MRT project in Singapore - Rajeevan Kuniyil Thazhe (2008)
Methods of tunnel construction in soft ground have been developed to the extent that it is possible to drive tunnel in difficult geological condition with minimum settlement. Improved tunneling practices are linked very much to progress in excavation technique. More effective ground control together with improvements in the working environment have also played important role in accomplishing successful tunnelling projects in increasingly difficult geological condition.